The K-Th derivatives of the immanant and the X-symmetric power of an operator - Carvalho, Sonia (2015)
In recent papers, formulas are obtained for directional derivatives, of all orders, of the determinant, the permanent, the m-th compound map and the m-th induced power map. This paper generalizes these results for immanants and for other symmetric powers of a matrix.